UJI AKTIVITAS REPELAN MINYAK ATSIRI BUAH LILIGUNDI (Vitex trifolia Linn) TERHADAP NYAMUK AEDES AEGYPTI - Sugiri Adiyasa, I Wayan; Santi, Sri Rahayu; Manurung, Manuntun (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014, 2014)
The isolation and repellent activity of essential oil extracted from fruit of Vitex trifolia against Aedes aegypti has been done. Distillation of 15 kg samples produced 7,6 mL essential oils with 0,819 ± 0,05 g/mL of density and 0,0418% ± 0,01% (b/b) of yields. Identification with Gas Chromatography-Mass Spectrometry results showed that the essential oil composed of 16 compounds  and was a rich source of ?-Pinene, Sabinene, 1,8-Cineol, and ?-Charyophyllene. Varied concentrations of the essential oil of 7,5%, 15%, and 20% solution in 96% ethanol and DEET 15% as positive control were tested for their repellent activities against Aedes aegypti . The result of ANOVA test showed that there was significant difference in protection abilities amongst the essential oil solutions for 6 hour test. The result of Tukey/HSD test showed that 15% and 20% of essential oils solutions possesed repellent activity as strong as positive control at first test and the 20% of essential oils solution possesed repellent activity as strong as positive control at first hour. Based on the above results it can be concluded that the essential oil of Vitex trifolia fruit posseses repellent activity against Aedes aegypti .
Keywords: Essential oils, fruit of Vitex trifolia, mosquito repellent, Aedes aegypti